Can Isoflurane and Meloxicam Mitigate Pain Associated with Cautery Disbudding of 3-Week-Old Goat Kids? - Melissa N. Hempstead; Joseph R. Waas; Mairi Stewart; Vanessa M. Cave; Mhairi A. Sutherland (Animals, 2020)
We evaluated the effect of pain mitigation strategies (isoflurane and meloxicam) on the behaviour and physiology of 3-week-old disbudded goat kids. Fifty Saanen does (mean ± SD, 21 ± 3 days old) were randomly allocated to one of five treatments: (1) cautery-disbudded (CAUT), (2) CAUT + isoflurane (ISO), (3) CAUT + isoflurane + meloxicam (ISO + MEL), (4) CAUT + meloxicam (MEL), and (5) handled without disbudding or pain relief (SHAM). Blood samples were taken immediately prior to treatment and at 15-, 60- and 120-min post-treatment to assess cortisol, glucose and lactate concentrations. Behaviour (head shaking and scratching, body shaking, feeding and self-grooming) was observed for 1 h pre- and post-treatment using video-cameras. ISO + MEL and ISO kids had lower cortisol concentrations than CAUT kids 15 min post-treatment (p ≤ 0.05). There was no effect of treatment or time for glucose and lactate concentrations (p ≥ 0.62). At 35 min post-treatment, CAUT, MEL and ISO kids performed more head shakes than SHAM kids (p ≤ 0.05). Isoflurane, with or without meloxicam, may reduce acute stress associated with disbudding of 3-week-old goat kids. More research is needed to assess whether isoflurane (with or without meloxicam) can provide sufficient pain relief for disbudding 3-week-old kids.